PENGARUH PENAMBAHAN INISIATOR DIKUMIL PEROKSIDA DAN DIVINILBENZENA SEBAGAI CROSLINK PADA KOMPATIBILITAS RASIO CAMPURAN POLIETILENA DAN KARET ALAM SIR 3L - Amir Hamzah Siregar (JURNAL KIMIA MULAWARMAN, 2010)
The research about  the influence of adding initiator dicumyl peroxide and divinylbenzene as crosslink agent on the compatibility blending rasio polyethylene and natural rubber SIR 3L   has been carried out. Blending is done in two steps, the first step was without the addition of divinylbenzene, polyethylene/natural rubber SIR 3L/dicumyl peroxide (w/w) 50 g : 50 g : 1phr, 2phr, and 3phr. The second step was by the addition of divinylbenzene, polyethylene/natural rubber SIR 3L/divinylbenzene/dicumyl peroxide (w/w) 50 g : 50 g : 1phr :1phr, 2phr : 1phr, 3phr : 1phr, 1phr : 2 phr, 2phr : 2phr, 3phr : 2phr, 1phr : 3phr, 2phr : 3phr, dan 3phr : 3phr. To determine the quality of yielded composites,  the tensile test analysis was done, obtained the increasing concentration without divinylbenzene, maximum at variation of concentration polyethylene/natural rubber SIR 3L/dicumyl peroxide is 2 phr is tensile strength and elasticity was 2.20 kgf/mm2 and 12.29%, and by addition of divinylbenzene  obtained the increasing maximum at variation of concentration polyethylene/natural rubber SIR 3L/divinylbenzene/dicumyl peroxide 3phr : 2phr, the tensile strength and elasticity was 3.31 kgf/mm2 and 28.99%. From the SEM analysis result was obtained that the addition of divinylbenzene could improved the composite’s surface so that  become more flatten and homogeneous. From the functional group analysis FT-IR showed that the mixture of divinylbenzene and polyethylene/natural rubber SIR 3L/dicumyl peroxide were just physical interaction. Keyword: peroxside,  Divinyl benzene, Poly Ethylene, Natural rubber (SIR 3 L) Blending